10 Psalms to help you pray like Jesus - Mahoney, Anne Louise; Georges, Helene; Saillard, Remi; Perrin, Clotilde; Balicevic, Didier; Renon, Delphine; Gaste, Eric (Bayard, 2009)
This book features 10 prayers with illustrations based on 10 Psalms to help readers pray like Jesus.